Ready for another leap? Making a case for tetrads. Issue 2 (March 2023) - Choi, Thomas Y.; Holmen, Elsebeth
Abstract: Tetrads are more conducive to studying the dynamic nature of supply networks compared to triads. For instance, the balance theory assumes there is equilibrium in the triadic structure when, in fact, relationships are constantly in flux in networks. Tetrads help us examine how a network is embedded in a larger network, how factions or subgroups operate in networks, and how strong and weak ties play out in a network. Highlights: There are important network dynamics that we may not be able to address in triads that we may be in tetrads. With the addition of one more node, we can see how a triad is now embedded in another network (i.e., a tetrad), how a faction of two nodes faces off another faction of two, and how two against two plays out in strong and weak ties.